Assessing the impact of the European resilience curriculum in preschool, early and late primary school children - Simões, Celeste (2021)
Resilience is an individual’s ability to adapt successfully to and persevere during and after significant challenges. Resilience programmes based on a socioemotional learning approach have been associated with an increase in protective factors (e.g., prosocial competencies), improvements in physical and mental health, and a decrease in internalised and externalised symptoms. The present study aimed to evaluate the impact of the RESCUR curriculum implemented in Portuguese schools on students’ academic, behavioural, and socioemotional outcomes, based on child and teacher reports. Participants included 1,084 children (53.2% male) aged 3-15 (M¼7.24, SD¼2.31). A quasi-experimental study compared outcomes for an experimental intervention group (AIG) with a waiting list control group (WG). The results showed the RESCUR programme decreased mental health difficulties while increasing both prosocial behaviours and well-being. In addition, academic performance increased for those in preschool after implementation. Both teachers and children consistently reported positive behavioural changes in resilience-related competencies after implementing RESCUR. Our findings contribute to the recent research on the potential of RESCUR to address key socioemotional competencies and improve relevant protective factors. Study limitations and future recommendations are addressed.